A produção do urbano e do imobiliário na região metropolitana de Belém - Luiz Augusto Soares Mendes (Confins)
This article deals with the urban-real estate dynamics that produces the Metropolitan Region of Belém in the State of Pará (RMB) assuming several fronts of expansion. It seeks to understand the closure of the urban real estate frontier on one side of the metropolitan space, in Belém, and its expansion on the other, in the other cities that make up the region. It presents the various real estate actions and the spatialization of its various products, seeking to show its relations with the cities that make up the RMB and the expansion of a real estate sector that is structured in a different way. This spatialization is the result of on-the-spot observations, analysis of documents in newspapers, interviews, application of questionnaires and forms. These methodological actions culminated in a thorough analysis of urban realities, in which urban extensification and dispersion were identified on the one hand, as well as the intensification and concentration of the urban on the other side.